Exequatur procedure of foreign judgement about surrogacy: comments on the judicial decree of the Barcelona Provincial Court (12th Section-Civil), issued on december 18, 2019 - Vilar González, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper examines a Judicial Decree of the Barcelona Provincial Court, issued on December 18, 2019, which allows the appeal against the non-admission in limine litis of an application for recognition of a foreign decision. The non-admission was based on the fact that, since the foreign decision was related to a surrogacy process, it was considered contrary to Spanish public policy and was therefore rejected. Nevertheless, as the Spanish Supreme Court has indicated on several occasions, claims may only be rejected in the cases and for the reasons provided for by law, and it is up to the Courts to guarantee the fundamental right to effective judicial protection.
Keywords: This paper examines a Judicial Decree of the Barcelona Provincial Court; issued on December 18; 2019; which allows the appeal against the non-admission in limine litis of an application for recognition of a foreign decision. The non-admission was based on